2022
DOI: 10.1111/jns.12483
|View full text |Cite
|
Sign up to set email alerts
|

SARM1 knockout does not rescue neuromuscular phenotypes in a Charcot‐Marie‐Tooth disease Type 1A mouse model

Abstract: Charcot-Marie-Tooth disease Type 1A (CMT1A) is caused by duplication of the PMP22 gene and is the most common inherited peripheral neuropathy. Although CMT1A is a dysmyelinating peripheral neuropathy, secondary axon degeneration has been suggested to drive functional deficits in patients. Given that SARM1 knockout is a potent inhibitor of the programmed axon degeneration pathway, we asked whether SARM1 knockout rescues neuromuscular phenotypes in CMT1A model (C3-PMP) mice. CMT1A mice were bred with SARM1 knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…PMP22 is a Schwann cell-enriched gene and even though CMT1A and HNPP pathogenesis initially occurs in myelinating Schwann cells, secondary axon degeneration as a consequence of myelin dysfunction has been suggested to drive functional deficits in patients 4,5 . However, our previous results with CMT1A model mice revealed negligible evidence of denervation and secondary axon degeneration despite their strong neuromuscular behavioral deficits, dramatically reduced tibial nerve CMAP amplitudes (~50%) and muscle atrophy as determined by gastrocnemius muscle fiber cross sectional area and total muscle mass 6 . These findings indicated that primary myelin dysfunction may play a critical role in driving CMT1A pathogenesis and provided rationale for investigating mechanisms of myelin dysfunction in CMT1A and HNPP model mice.…”
Section: Introductionmentioning
confidence: 71%
“…PMP22 is a Schwann cell-enriched gene and even though CMT1A and HNPP pathogenesis initially occurs in myelinating Schwann cells, secondary axon degeneration as a consequence of myelin dysfunction has been suggested to drive functional deficits in patients 4,5 . However, our previous results with CMT1A model mice revealed negligible evidence of denervation and secondary axon degeneration despite their strong neuromuscular behavioral deficits, dramatically reduced tibial nerve CMAP amplitudes (~50%) and muscle atrophy as determined by gastrocnemius muscle fiber cross sectional area and total muscle mass 6 . These findings indicated that primary myelin dysfunction may play a critical role in driving CMT1A pathogenesis and provided rationale for investigating mechanisms of myelin dysfunction in CMT1A and HNPP model mice.…”
Section: Introductionmentioning
confidence: 71%
“…Whether SARM1 inhibition could also apply to CMT is still under investigation. In this respect, it has been recently shown that SARM1 deletion does not rescue the behavioral, neurophysiological, or morphological phenotype of the C3‐PMP22 mice, a model of CMT1A 134 . However, contrary to humans affected by CMT1A that experience significant axonal loss as disease progresses, the C3 mouse model is mostly affected by severe dysmyelination and shows little to no axonal degeneration, 134 at least at the relatively early adults time points analyzed in the study.…”
Section: Pharmacological Approaches For Axonal Cmt2mentioning
confidence: 81%
“…In this respect, it has been recently shown that SARM1 deletion does not rescue the behavioral, neurophysiological, or morphological phenotype of the C3-PMP22 mice, a model of CMT1A. 134 However, contrary to humans affected by CMT1A that experience significant axonal loss as disease progresses, the C3 mouse model is mostly affected by severe dysmyelination and shows little to no axonal degeneration, 134 at least at the relatively early adults time points analyzed in the study. This finding renders these results hard to interpret and indicates the need to analyze the mice at later time points and possibly the necessity for improved CMT1A models.…”
Section: Sarm 1 Inactivation To Prevent Axonal Degeneration In Cmt2mentioning
confidence: 88%
“…The number and density of myelinated axons (healthy axons surrounded by a myelin sheath) were evaluated from four randomly placed squares of equal area in the tibial branch of the sciatic nerve with ImageJ. 46 , 49 Nerve electrophysiology and morphometry results were averaged and compared between alive transplanted hESC- and iPSC-derived Schwann cells (n=2-4/stem cell line, n=8-12 total) and between heat killed transplanted hESC- and iPSC-derived Schwann cells (n=5-3 total) by unpaired t-test. Transplanted hESC- and iPSC-derived Schwann cell results were also pooled and compared between alive and heat killed cells by unpaired t-test with Welch correction for unequal variance (significant p<0.05, Prism 9).…”
Section: Methodsmentioning
confidence: 99%